P29 Out of control? Experiences of transitions between care settings at the end of life for older adults with heart failure: a qualitative study. (16th November 2010) - Holmes, L; Addington-Hall, J; Grande, G; Payne, S; Seymour, J; Hanratty, B
Abstract : Background: Transitions between care settings have been associated with poor continuity and quality of care for older people. Movements between places of care occur frequently in the months before death, making them an important influence on well-being and health status. People with heart failure may be particularly likely to experience frequent, unplanned admissions to hospital. Objective: To explore and understand experiences of care transitions for older adults with heart failure at the end-of-life. Design: In-depth qualitative interviews with 35 people with heart failure, lung cancer or stroke. Framework methodology was used for data analysis. Participants: Fifteen adults aged over 75 years with heart failure, whose hospital clinician answered "no" to the question, would you be surprised if this patient dies within the next 12 months? Half the participants were from socially disadvantaged backgrounds. Findings: Participants described how they struggled to have control over many of their end of life experiences. Their ability to negotiate their role with professionals, family and the wider world was threatened by their biographical experiences and physical helplessness. Long-standing relationships with family doctors were associated with low expectations and a perceived loss of control, particularly for the most disadvantaged people. A majority had lost all trust in their GPs, and the doctor was allowed to share in symptom management only when severe—preserving some autonomy for the older person, but threatening physical health and future choices. The rest had taken on the role of passive recipients of advice and treatment. Frequent admissions to hospital were tainted by the perception of being a burden to staff reluctant to help with basic care, and families obliged to visit. Conclusions: Notions of choice and empowerment prevalent in current health policy discourses appeared to have little relevance to the lived experiences of the older adults in this study. Without an understanding of biographical and social context, analyses of how older people experience health and social care at the end-of-life risk promoting concepts of individual control that many older adults do not enjoy. If end-of-life care policies are to produce equitable outcomes, they must go beyond simple solutions to address the complexity of relationships older adults have developed with health services over their lifetimes.